FORTRAN PROGRAM FORECASTING ON MATERNAL MORTALITY IN TYPE C HOSPITALS IN EAST JAVA BASED ON PREDOMINANT VARIABLES - Atmadja, Sardjana; Gumilar, Gulam (ADI Journal on Recent Innovation (AJRI), 2019)
In Indonesia, the effort to reduce maternal mortality rate remains unsatisfactory and is progressing slowly due to the lack of working ethos, blood facility, communication facility, obstetrician and gynecologists, midwifes, nurses, and functionaries of Indonesian Red Cross. Objective. To forecast maternal mortality in all type C hospitals in East Java, 2010 - 2015. Material and Methods. This study was a development of clinical management from predominant variables that lead to maternal mortality in type C hospitals in East Java using FORTRAN simulation program. Results. The contribution of working ethos to clinical management model in reducing maternal mortality in governmental type C hospital was 45.46%, indicating that the contribution if this variable can be expandable to 57.99%. The contributions of blood facility and communication facility were 27.22% and 26.95%, indicating a possible expanding contribution as much as 34.73% and 34.38% respectively.